KEBIJAKAN INSENTIF PAJAK PENGHASILAN BAGI UMKM DI DIY: REALISASI DAN RELEVANSINYA DENGAN PRINSIP KESAMAAN DALAM PERPAJAKAN - Hasan, Dahliana; Nugroho, Adrianto Dwi (Jurnal Kajian Ekonomi dan Keuangan, 2010)
The tax incentive indirectly provided for micro, small and medium enterprises as laid down in Article 31E of the Income Tax Act is indicated of being discriminative, as the incentive will only be provided for Resident Corporate Taxpayer. Moreover, the policy is also considered ineffective, as many micro, small, and medium enterprises in Indonesia are roughly consisted of Individual Taxpayers. Therefore, there is a need for conducting a further study on the policy and perhaps formulating a better tax incentive policy for micro, small and medium enterprises in the future.This research aims at analyzing and providing an elaborative description on whether or not the tax incentive laid down in Article 31E of the Income Tax Act has violated the principle of equality in taxation, in which taxpayers being in the same circumstances shall be treated the same, and taxpayers not being in the same circumstances shall not be treated the same. Moreover, the research also aims at reviewing the implementation of the policy in Yogyakarta, Bantu!, and Sleman regencies within the 2009 Fiscal year. Based on the results of the above research, this research will attempt at formulating a better tax incentive policy for micro, small and medium enterprises in the future.The results show that even though the policy specifically targeted at Resident Corporate Taxpayers, it nevertheless upholds the principle of equality in taxation. Moreover, the implementation of the policy in three regencies in D1 Yogyakarta Province may not be evaluated yet, as the 2009 Fiscal Year has not ended, and taxpayers would only have to submit their tax files on April 2010 at the latest Lastly, in the future, the Government and the House of Representatives shall be able to formulate a better tax incentive policy for micro, small and medium enterprises by, among others, targeting the policy at such enterprises carried on by Resident or Nonresident Individual Taxpayers.